Endurance of gel-filled silicone breast implants as a function of maximum load in cyclic compression tests - von Hanstein, Harald; Horch, Raymund E.; Schubert, Dirk W. (Polymer International, 2019)
The mechanical behaviour of gel‐filled silicone breast implants is examined under compressive load. First the implants are tested by applying various loads in a repetitive fashion until shell rupture occurs. Subsequently the results are presented allowing an assessment of the correlation between the number of loading cycles and the maximum compressive load. Finally it is possible to estimate the endurance of the silicone breast implants. Using a power law, a correlation between endurance and maximum load is revealed
CRIS-Team WoS Importer:2019-04-04
Keywords: Silicone breast implant; mechanical behavior; compression test; mechanical loading; endurance